Une vocation à aimer l’invalide. La mobilisation ratée de Jean Adnet - Pierre Brasseur (Genre, Sexualité et Société)
In France, since the early 2000s, groups of people with disabilities have mobilized in order to elaborate new ways of thinking about their sexuality and about what a "sexual condition" of the disabled might look like. This paper proposes a socio-historical analysis of that situation: it looks into the 1950s and particularly into the writings of Jean Adnet, a disabled activist, who fought for the development of forms of love for the disabled. This case goes to show how the sex and love lives of the disabled were considered; it is also the description of a sexual protest, its trajectory, and then its failure.